Indonesian Spatial Planning After the Enactment of the Job Creation Law as a Formulation Effort Towards the Society Era 5.0 - Adi Gunawan; Adriana Pakendek; Win Yuli Wardani; Sri Sulastri; Achmad Taufik; Nadir (International Journal of Science and Society, 2022)
Entering the society era 5.0, which is based on a computerized program, the Indonesian Government ratified Law No. 11 of 2020 concerning Job Creation to increase the absorption of the number of Indonesian workers by creating job opportunities through investors with the ease and facilities provided by the Government, using a computer program system. This research was normative legal research that used statutory and conceptual approaches. Additionally, it used qualitative analysis, then concluded using deductive-inductive reasoning. Based on the research results, it was found that the Government formulated Job Creation Law to implement a new system in the licensing sector using the OSS (Online Single Submission) system as a business licensing system controlled by the central Government and applied to all provincial or district governments. One of the objects regulated in the Job Creation Law and using the OSS system was Spatial Planning. The first revision in spatial planning regarded the implementation, which clarified the tiered and complementary system. Furthermore, the decision-making related to the performance of regional spatial planning in the district or province was on the central Government.